PROMOSI PRODUK DI FACEBOOK MELALUI COMMUNITY MARKETING - Risky, Mohammad (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2020)
Facebook is a medium for promotion to consumers who join community marketing. Community marketing uses Facebook to promote goods or services, making it easy to access almost everyone who has a Facebook account. Another advantage is that the number of members is not limited so that community marketing that synchronizes with the group can promote products to all users who can view the community marketing group. Producers become members of Facebook like users in general. Producers who become members of Facebook can promote their products repeatedly, greet and chat with their consumers so that there is a close relationship between producers and consumers. The purpose of this research is to find out promotions carried out on Facebook through community marketing. This type of research is descriptive qualitative research based on source analysis. The research subject is purposive sampling. The data collection techniques used were participant observation, in-depth interviews. The research results show that promotion carried out by community marketing on Facebook is a process in an online community on Facebook which aims to promote their goods or products to potential consumers who are members of the community. The process of promoting products on Facebook through community marketing uses three promotional techniques, namely Sales Promotion, implementing promotions such as attractive displays, price discounts and samples such as making video demos of the items being promoted. Direct Marketing or direct marketing is an interactive process between consumers and marketers by establishing communication to then get a response as soon as possible from consumers using various media that are not limited to using only one type of media and are closed in nature. Mouth to Mouth is a way of spreading information about goods or services through chat from one person to another, such as sellers promoting each other and the same is done by consumers giving each other information about the products or goods offered by the seller.